Distributed Computing in Sensor Systems 6th IEEE International Conference, DCOSS 2010, Santa Barbara, CA, USA, June 21-23, 2010. Proceedings - Rajaraman, Rajmohan; Moscibroda, Thomas; Dunkels, Adam.; Scaglione, Anna.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The book constitutes the refereed proceedings of the 6th International Conference on Distributed Computing in Sensor Systems, DCOSS 2010, held in Santa Barbara, CA, USA, in June 2010. The 28 revised full papers presented were carefully reviewed and selected from 76 submissions. The research contributions in this proceedings span important aspects of sensor systems, including energy management; communication; coverage and tracking; time synchronization and scheduling; key establishment and authentication; compression; medium access control; code update; and mobility.
Tables: A Spreadsheet-Inspired Programming Model for Sensor Networks -- Optimized Java Binary and Virtual Machine for Tiny Motes -- ZeroCal: Automatic MAC Protocol Calibration -- Programming Sensor Networks Using Remora Component Model -- Stateful Mobile Modules for Sensor Networks -- Design and Implementation of a Robust Sensor Data Fusion System for Unknown Signals -- Control Theoretic Sensor Deployment Approach for Data Fusion Based Detection -- Approximate Distributed Kalman Filtering for Cooperative Multi-agent Localization -- Thermal-Aware Sensor Scheduling for Distributed Estimation -- Decentralized Subspace Tracking via Gossiping -- Building (1????) Dominating Sets Partition as Backbones in Wireless Sensor Networks Using Distributed Graph Coloring -- On Multihop Broadcast over Adaptively Duty-Cycled Wireless Sensor Networks -- A Novel Mobility Management Scheme for Target Tracking in Cluster-Based Sensor Networks -- Suppressing Redundancy in Wireless Sensor Network Traffic -- Ensuring Data Storage Security against Frequency-Based Attacks in Wireless Networks -- Time-Critical Data Delivery in Wireless Sensor Networks -- MetroTrack: Predictive Tracking of Mobile Events Using Mobile Phones -- Mobile Sensor Network Localization in Harsh Environments -- AEGIS: A Lightweight Firewall for Wireless Sensor Networks -- Halo: Managing Node Rendezvous in Opportunistic Sensor Networks -- Optimal Data Gathering Paths and Energy Balance Mechanisms in Wireless Networks -- Programming Sensor Networks with State-Centric Services -- Fast Decentralized Averaging via Multi-scale Gossip -- Wormholes No More? Localized Wormhole Detection and Prevention in Wireless Networks -- Wireless Jamming Localization by Exploiting Nodes$1 (BHearing Ranges -- Self-stabilizing Synchronization in Mobile Sensor Networks with Covering -- Sensor Allocation in Diverse Environments -- Data Spider: A Resilient Mobile Basestation Protocol for Efficient Data Collection in Wireless Sensor Networks.s
Keywords: Computer science; Computer communication systems; Software engineering; Operating systems (Computers).; Algorithms; Information storage and retrieval; Computer Science; Computer Communication Networks; Information Systems Applications (incl. Internet).; Algorithm Analysis and Problem Complexity; Software Engineering; Information Storage and Retrieval; Operating Systems; Electronic books